Debonding of a weak interface in front of a through-thickness crack - Korsunsky, A (Springer Science+Business Media, 2001)
A through thickness crack traversing a laminate and approaching an interface weakened by the presence of a small debonding defect is analysed in the case when the defect is fully embedded in the K -field of the main crack. Plane approximation estimates of critical interfacial strength for crack deflection are compared with 3D calculations using integral equation and weight function formulations.